Patients' Attitudes Towards Disclosure of Genetic Test Results to Family Members: The Impact of Patients' Sociodemographic Background and Counseling Experience. Issue 2 (14th September 2015) - Gilbar, Roy; Shalev, Stavit; Spiegel, Ronen; Pras, Elon; Berkenstadt, Michal; Sagi, Michal; Ben‐Yehuda, Adi; Mor, Pnina; Perry, Shlomit; Zaccai, Tzipora Falik; Borochowitz, Zvi; Barnoy, Sivia
Abstract: Many factors predict the intention to disclose genetic information to relatives. The article examines the impact of patients' socio‐demographic factors on their intention to disclose genetic testing results to their relatives. Data were collected in eight genetic clinics in Israel. Patients were requested to fill in a questionnaire after counseling. A convenience sample of 564 participants who visited these clinics was collected for a response rate of 85 %. Of them, 282 participants came for susceptibility testing for hereditary cancers (cancer group), and 282 for genetic screening tests (prenatal group). In the cancer group, being secular and having more years of education correlated positively with the intention to disclose test results to relatives. In the prenatal group, being married and female correlated positively with the intention to disclose. In the cancer group, being religious and with less years of education correlated positively with the view that the clinician should deliver the results to the family. In the prenatal group, being male and unmarried correlated positively with this belief. In both groups, being of young age correlated with the perception that genetic information is private. Varied sociodemographic factors affect the intention to inform family members. Thus, knowing the social background of patients will shed light on people's attitudes to genetic information and will help clinicians provide effective counseling in discussions with patients about the implications of test results for relatives.